Elastic impact of sphere on large plate. (November 2021) - Peng, Qing; Liu, Xiaoming; Wei, Yueguang
Highlights: The Zener impact was solved by using homotopy analysis method. Structural compliance breaks contact force symmetry. Zener energy loss is proportional to the impact velocity to the power of 0.2. Abstract: Different from the Hertz impact, a sphere impacting on a plate has an extra dissipation by the flexural wave propagating on the plate. This wave dissipation has been noticed by Zener (1941), who introduced this dissipation term into the governing equation. Because of this extra dissipation term by the flexural wave, the Zener equation cannot be treated as the same way as in the Hertz impact problem. As a result, in the past 80 years, except few numerical tries for Zener equation, no analytical solution has been provided for the evolution of compressive displacement or contact force during the Zener impact. In this paper, by using homotopy analysis method, we analytically solved the Zener impact problem. After constructing an auxiliary linear operator, we derived an analytical solution for the evolution of contact force up to the first order of the embedding homotopy parameter. Present model can take full account of the elongation of contact time by plate compliance, which is impossible by using Hertz impact model. Comparisons with finite element simulation show that the prediction of the contact force history is of high accuracy. With the solution of force history, we derived an explicit expression for the energy loss of Zener type, this Zener loss has a different dependence on the impact velocity as the Hunter loss does. Also, both the motions of the sphere and the plate are able to be predicted with high accuracy. In addition, with the zeroth-order solution, we derived explicit expressions for both the coefficient of restitution and the contact duration. Graphical abstract: Image, graphical abstract